Thermoluminescence and EPR study of K2CaMg(SO4)3:Dy phosphor: the dosimetric application point of view. (1st February 2016) - Kore, Bhushan P; Dhoble, N S; Kadam, R M; Lochab, S P; Singh, M N; Dhoble, S J; Swart, H C
Abstract: A detailed investigation of the thermoluminescence (TL) properties of γ -ray and C 5+ ion beam irradiated K2 CaMg(SO4 )3 :Dy (KCM) phosphor was carried out. KCM was irradiated by 50 and 75 MeV energy C 5+ ion beams with a fluence range of 15 × 10 10 ions cm −2 to 30 × 10 12 ions cm −2 . The TL glow curves along with the response curves of these phosphor samples were analyzed and compared with commercial CaSO4 :Dy phosphor. The TL glow curves of the phosphor exposed to γ -rays from 60 Co and 137 Cs sources were also examined in this study for comparative analysis. Theoretical analysis of the glow curves of the C 5+ ion beam and γ -ray irradiated samples was performed using the glow curve deconvolution method. SRIM/ TRIM simulations were performed in order to identify the ion beam profile, range, distribution, etc. The enhancement in the intensity of the low temperature glow peak is explained with the help of an energy level model and the decrease in TL intensity with increasing ion fluence is also explored in detail. The radicals produced after irradiation were verified using the electron paramagnetic resonance (EPR) technique. The effects of temperature and microwave power on the EPR signal are also studied.